Penanaman Kreativitas Berwirausaha Peserta Didik Melalui Kebun Hidroponik - Candrasari, Tri Ratna (Pena Edukasia, 2023)
Realizing the vision of SD Negeri Tanjung Mas, which is superior in achievement, skilled, commendable in character, friendly, and cultured in an environment based on faith and piety. Seeing the potential of the environment around the school which is in a densely populated area with limited land, close to industrial areas and ports, the livelihoods of the local residents are mostly private employees, trading. So that SD Negeri Tanjung Mas implements an entrepreneurship learning program through hydroponic gardens. The entrepreneurship learning program through the hydroponic garden aims to stimulate the creativity of students at SD Negeri Tanjung Mas and provide skills for entrepreneurship. The purpose of this writing is to find out the entrepreneurship learning program with hydroponic gardens at Tanjung Mas State Elementary School and to find out the creativity of students contained in the implementation of entrepreneurship learning programs with hydroponic gardens. This writing is included in the type of qualitative descriptive writing. The subjects in this study were grade 5 students, teachers, and parents of students at SD Negeri Tanjung Mas Semarang. Data collection methods used in this writing are interviews, observation, and documentation. The results of this literature study and exploratory study are on the entrepreneurship learning program with hydroponic gardens implemented by SD Negeri Tanjung Mas and the creativity of students contained in the implementation of entrepreneurship learning through hydroponic gardens. The implementation of the entrepreneurship learning program with hydroponic gardens consists of three main activities, namely planting activities, market day activities, and harvesting activities. These three core activities implement entrepreneurial values, namely independence, creativity, courage to take risks, action-oriented, leadership, and hard work. Creativity in students contained in the implementation of entrepreneurship learning with hydroponic gardens can be seen from having original ideas, being rich in initiative, seeing a problem and solving the problem, having different skills, thinking critically and being curious, responsibility and commitment to the task , confident and also independent.